Decreased Levels of Circulating IL17-Producing CD161+CCR6+ T Cells Are Associated with Graft-versus-Host Disease after Allogeneic Stem Cell Transplantation - van der Waart, Anniek B.; van der Velden, Walter J. F. M.; van Halteren, Astrid G. S.; Leenders, Marij J. L. G.; Feuth, Ton; Blijlevens, Nicole M. A.; van der Voort, Robbert; Dolstra, Harry (PLOS ONE, 2012)
The C-type lectin-like receptor CD161 is a well-established marker for human IL17-producing T cells, which have been implicated to contribute to the development of graft-versus-host disease (GVHD) after allogeneic stem cell transplantation (allo-SCT). In this study, we analyzed CD161+ T cell recovery, their functional properties and association with GVHD occurrence in allo-SCT recipients. While CD161+CD4+ T cells steadily recovered, CD161hiCD8+ T cell numbers declined during tapering of Cyclosporine A (CsA), which can be explained by their initial growth advantage over CD161neg/lowCD8+ T cells due to ABCB1-mediated CsA efflux. Interestingly, occurrence of acute and chronic GVHD was significantly correlated with decreased levels of circulating CD161+CD4+ as well as CD161hiCD8+ T cells. In addition, these subsets from transplanted patients secreted high levels of IFNγ and IL17. Moreover, we found that CCR6 co-expression by CD161+ T cells mediated specific migration towards CCL20, which was expressed in GVHD biopsies. Finally, we demonstrated that CCR6+ T cells indeed were present in these CCL20+ GVHD-affected tissues. In conclusion, we showed that functional CD161+CCR6+ co-expressing T cells disappear from the circulation and home to GVHD-affected tissue sites. These findings support the hypothesis that CCR6+CD161-expressing T cells may be involved in the immune pathology of GVHD following their CCL20-dependent recruitment into affected tissues.